Inner heliosphere MHD modeling system applicable to space weather forecasting for the other planets. Issue 4 (2nd April 2014) - Shiota, D.; Kataoka, R.; Miyoshi, Y.; Hara, T.; Tao, C.; Masunaga, K.; Futaana, Y.; Terada, N.
<x xml:space="preserve">Abstract</x> We developed a magnetohydrodynamic (MHD) solar wind model which can be used for practical use in real‐time space weather forecasting at Earth's orbit and those of other planets. The MHD simulation covering 3 years (2007–2009) was performed to test the accuracy, and the numerical results show reasonable agreement with in situ measurements of the solar wind at Earth's orbit and with measurements at Venus and Mars by Venus Express and Mars Express, respectively. The comparison also shows that the numerical results can be used to detect stream interfaces, which is useful for space weather forecast of killer electrons in the outer Van Allen belt.